2018
DOI: 10.1039/c8fd00059j
|View full text |Cite
|
Sign up to set email alerts
|

Real-time determination of aggregated alpha-synuclein induced membrane disruption at neuroblastoma cells using scanning ion conductance microscopy

Abstract: Parkinson's disease (PD) is recognized as the second most common neurodegenerative disorder and has affected approximately one million people in the United States alone. A large body of evidence has suggested that deposition of aggregated alpha-synuclein (α-Syn), a brain protein abundant near presynaptic termini, in intracellular protein inclusions (Lewy bodies) results in neuronal cell damage and ultimately contributes to the progression of PD. However, the exact mechanism is still unclear. One hypothesis is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 50 publications
3
5
0
1
Order By: Relevance
“…These pores were not static and appeared at different locations at each time point; we attribute this observation to the fluidity of the lipid bilayer. These findings support the proposition that higher concentrations of α-Syn oligomers increase tension on the membrane to open transient, micrometer-scale pores, as previously observed at similar concentrations in supported lipid bilayers (2.5 μM α-Syn) and fixed cells (2 and 10 μM α-Syn). , Additionally, several small features were observed to form on the membrane; these features may represent the extraction of membrane lipids to form protein/lipid clusters on the surface of the cell, as previously observed in supported lipid bilayers (3.0 μM α-Syn) …”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…These pores were not static and appeared at different locations at each time point; we attribute this observation to the fluidity of the lipid bilayer. These findings support the proposition that higher concentrations of α-Syn oligomers increase tension on the membrane to open transient, micrometer-scale pores, as previously observed at similar concentrations in supported lipid bilayers (2.5 μM α-Syn) and fixed cells (2 and 10 μM α-Syn). , Additionally, several small features were observed to form on the membrane; these features may represent the extraction of membrane lipids to form protein/lipid clusters on the surface of the cell, as previously observed in supported lipid bilayers (3.0 μM α-Syn) …”
Section: Resultssupporting
confidence: 90%
“…However, other publications have suggested that membrane permeabilization by α-Syn oligomers is less discrete and only occurs after a critical amount of protein has bound the membrane. These works have proposed that the binding of α-Syn oligomers to the cell membrane disrupts lipid packing, alters membrane curvature, and extracts lipids from the membrane onto adsorbed aggregates. , These disruptions would impose tension on the membrane, whichwhen severe enoughwould be expected to open large pores stabilized by α-Syn oligomers at the pore edges; this mechanism is conceptually similar to that by which many antimicrobial peptides permeabilize membranes . Atomic force microscopy (AFM) imaging of supported lipid bilayers and fixed cells in the presence of α-Syn oligomers has suggested the formation of micrometer-scale pores in the membrane, supporting this “membrane destabilization” model. …”
Section: Introductionmentioning
confidence: 99%
“…The permeabilization of the plasma membrane upon interaction with protein oligomers has also been shown by electrophysiology studies of membrane conductance ( Feng et al, 2010 ). These observations are consistent with the formation of pores of different dimensions in the membrane upon treatment with oligomers ( Wong Su et al, 2018 ), as observed using atomic force microscopy ( Chaudhary et al, 2016 ; Oropesa-Nuñez et al, 2016 ; Bode et al, 2019 ). The ability to generate these pores has been associated to the exposure of hydrophobic regions ( Vivoli Vega et al, 2019 ) and the size of the protein oligomers ( Mannini et al, 2014 ; Chiti and Dobson, 2017 ).…”
Section: Disruption Of Biological Membranes By Toxic Protein Oligomersupporting
confidence: 88%
“…[57] ; (b) 活的海马神经元高分辨率SICM 成像 [19] ; (c) 单个纳米粒子与细胞膜相互作用动态过程观察的荧光和SICM形貌图 [60] ; (d) 玉米根毛细胞对[Ru(NH 3 ) 6 ] 3+ 的摄入 过程的SICM和SECM图像 [63] (网络版彩图) 呈现细胞表面形态及纳米颗粒内吞早期阶段的动态交 替过程. Su等 [62] [38] 、 心肌细胞 [39] 、上皮细胞 [30,69,70] 、成纤维细胞 [37,45] 、神 经元细胞 [32,71~74] 和胶质细胞 [75] 等. 例如, Happel等 [38] 使 用SICM观察到了在高渗和低渗溶液中肝细胞体积的 调节过程.…”
Section: 细胞拓扑形貌表征应用unclassified